2020
DOI: 10.1155/2020/6701272
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Patent Medicine for Primary Hypertension: A Bayesian Network Meta‐Analysis

Abstract: Background. Traditional Chinese Patent Medicine (TCPM) is now being used more and more extensively for primary hypertension in China. However, the comparative efficacy and safety of it need more clarified evidence. Thus, we conducted a Bayesian network meta-analysis to compare TCPMs with other interventions. Methods. We searched China National Knowledge Infrastructure (CNKI), WanFang Data, PubMed, Embase, and Cochrane Library from inception to April 2019 for randomized controlled trials (RCTs) with diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…As of now, we have identified 4 meta-analysis studies focused on the treatment of hypertension using CPMs, out of which, 2 studies [ 75 , 76 ] were classified as ordinary meta-analysis while the remaining 2 studies [ 77 , 78 ] were categorized as NMA. Ordinary meta-analysis solely focused on comparing a specific ginkgo-based CPM in combination with western medicine against the use of western medicine alone, and all these studies demonstrated the effectiveness of combining the medicines.…”
Section: Discussionmentioning
confidence: 99%
“…As of now, we have identified 4 meta-analysis studies focused on the treatment of hypertension using CPMs, out of which, 2 studies [ 75 , 76 ] were classified as ordinary meta-analysis while the remaining 2 studies [ 77 , 78 ] were categorized as NMA. Ordinary meta-analysis solely focused on comparing a specific ginkgo-based CPM in combination with western medicine against the use of western medicine alone, and all these studies demonstrated the effectiveness of combining the medicines.…”
Section: Discussionmentioning
confidence: 99%
“…In epidemiological studies, hypertension is considered to be an essential risk factor for cardiovascular mortality and morbidity [ 2 , 3 ], and its complications are now the most common cause of death in western countries [ 4 ]. Despite the significant progress in monitoring and drug treatment of hypertension [ 5 ], inadequate blood pressure control is still a serious public health problem at home and abroad [ 6 ].…”
Section: Introductionmentioning
confidence: 99%